Practical Guide to Dealing with Ethical Problems and Dilemmas: Strengthening Integrity in Peruvian Public Management - Manuel Villoria y César N. Cruz (2021)
The objective of this guide is to serve as support and assistance when Peruvian public servants are faced with ethical problems or dilemmas. A large part of the conflictive situations that people who work in the public administration may encounter would be resolved with a good knowledge of the applicable legal and ethical standards and their insertion into the Peruvian integrity and anti-corruption system. Consequently, this guide must be accompanied by a summary of the essential norms in matters of integrity that the Peruvian Administration has approved, so that the cases that arise can be analyzed, at first, from the comparison of the obligations. legal, in order to avoid that, due to ignorance, the people who use the guide can make legally incorrect decisions.